High performance anode-supported solid oxide fuel cell based on thin-film electrolyte and nanostructured cathode - Ding, Changsheng; Hashida, Toshiyuki (Energy & environmental science, 2010)
An anode-supported solid oxide fuel cell (SOFC) with a thin Gd 0.1 Ce 0.9 O 1.95 (GDC) electrolyte film of 3 μm in thickness and nanostructured La 0.8 Sr 0.2 Co 0.8 Fe 0.2 O 3 (LSCF) cathode showed high electrochemical performance at low operating temperatures, with a maximum power density of 0.99 W cm −2 at 600 °C using hydrogen as fuel. An anode-supported solid oxide fuel cell with thin Gd 0.1 Ce 0.9 O 1.95 electrolyte and nanostructured La 0.8 Sr 0.2 Co 0.8 Fe 0.2 O 3 cathode showed high electrochemical performance at low operating temperatures.